2019
DOI: 10.1186/s12986-019-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and metastasis inhibitory potential of pineapple vinegar against mouse mammary gland cells in vitro and in vivo

Abstract: Background Plant-based food medicine and functional foods have been consumed extensively due to their bioactive substances and health-beneficial effects. Vinegar is one of them due to its bioactivities, which confers benefits on human body. Our previous study has produced pineapple vinegar that is rich in gallic acid and caffeic acid via 2 steps fermentation. There are many evidences that show the effectiveness of these resources in inhibiting the proliferation and metastasis of the cancer cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Interestingly, 70 % of cell population underwent apoptosis and 30 % inhibited wound closure of 4T1 cells in response to the administration of PV. Therefore, anti-cancer efficacy of pineapple vinegar may be associated with the presence of phenolic acids, especially GA and CA in high content [65]. Moreover, methanol extracts of Anchusa azurea Mill, with CA as one of the four most abundant compounds, was found to induce programmed cell death in cancer cell line via activation of capsase-3/7 and -9 as well as modulation of cytoskeleton dynamics [66].…”
Section: Caffeic Acidmentioning
confidence: 99%
“…Interestingly, 70 % of cell population underwent apoptosis and 30 % inhibited wound closure of 4T1 cells in response to the administration of PV. Therefore, anti-cancer efficacy of pineapple vinegar may be associated with the presence of phenolic acids, especially GA and CA in high content [65]. Moreover, methanol extracts of Anchusa azurea Mill, with CA as one of the four most abundant compounds, was found to induce programmed cell death in cancer cell line via activation of capsase-3/7 and -9 as well as modulation of cytoskeleton dynamics [66].…”
Section: Caffeic Acidmentioning
confidence: 99%
“…AO: acridine orange; PI: propidium iodide development of colon carcinogenesis induced by azoxymethane was inhibited. Similarly,Mohamad et al (2019) indicated the potential anticancer activities of freeze-dreed coconut water vinegars in breast cancer cell model (4T1) as in vitro and in mice with breast cancer as in vivo. Accordingly, that study was pointed out that coconut water vinegars caused delay in breast tumor development by inducing apoptosis and also increasing in the inhibition of cell proliferation in 4T1.…”
mentioning
confidence: 99%
“…Cell apoptosis assay was conducted based on a study method [ 44 ] with some changes. Apoptosis of control and BHMC-treated MCF-7 cell was evaluated using AnnexinV-FITC/PI apoptosis detection kit (Becton Dickinson, USA).…”
Section: Methodsmentioning
confidence: 99%